Comparing the Dynamic Global Core Plasma Model with ground‐based plasma mass density observations. Issue 8 (3rd August 2017) - Jorgensen, Anders M.; Heilig, Balazs; Vellante, Massimo; Lichtenberger, Janos; Reda, Jan; Valach, Fridrich; Mandic, Igor
Abstract: The Dynamic Global Core Plasma Model (DGCPM) is an empirical dynamical model of the plasmasphere which, despite its simple mathematical form, or perhaps because of its simple mathematical form, has enjoyed wide use in the space physics modeling community. In this paper we present some recent observations from the European quasi‐Meridional Magnetometer Array (EMMA) and compare these with the DGCPM. The observations suggest more rapid daytime refilling and loss than what is described in the DGCPM. We then modify the DGCPM by changing the values of some of its parameters, leaving the functional form intact. The modified DGCPM agrees much better with the EMMA observations. The modification resulted in an order‐of‐magnitude faster daytime refilling and nighttime loss. These results are also consistent with previous observations of daytime refilling. Key Points: The Dynamic Global Core Plasma Model requires modification to agree with ground‐based magnetic observations in the inner magnetosphere We have proposed specific modifications to DGCPM to bring it into better agreement with observations The excellent agreement between the modified DGCPM and the EMMA observations support their use for plasmasphere sounding